La crónica deportiva como recurso de escritura en ELE/L2. Un enfoque procesual - Núñez-Román, Francisco; Emilio J. Gallardo-Saborido, Emilio J. Gallardo-Saborido (Studia Romanica Posnaniensia, 2020)
This paper stands up for the defence of writing as a hugely valuable resource for teaching Spanish as a Foreign Language or a Second Language. Specifically, it pursues two general targets: a) to highlight the importance of considering writing into the classroom of Spanish as a Foreign Language as a process that has to be constantly coached and developed; b) to emphasise how this way of teaching provides pedagogical benefits that go further the development of the writing ability itself, since it has an impact on other students’ general cognitive features. Methodologically, this text begins with a literature review that theoretically underpins the proposed targets, and, subsequently, our didactic proposal is exemplified by the use of a specific type of text (the match report). Then, a practical teaching resource is obtained as final result, which is supported by the recent literature on this issue. Finally, this contribution aspires to be implemented in different educative contexts by teachers of Spanish as a Foreign Language.